Peningkatan hasil belajar bermain Musik Ensambel sederhana melalui metode two stay two stray kelas VII. 1 SMP N 4 Siak Hulu Tahun Ajaran 2016/201 - Rosmawati, Rosmawati (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
The learning of music art is the learning of art and culture that seeks to explore and develop the aesthetic potential of learners as well as influence the students to have aesthetic value so that it can refine the character, because in the art there are elements of beauty, order, discipline and dynamics. Through learning approaches with art, learning through art, and learning about art, music art learning is given because of the uniqueness, meaningfulness, and usefulness of the development of learners in the form of giving the aesthetic experience in the form of expression / creative activities. The continuity of art and culture learning has also been optimized by serving the essential needs of artistry according to the talents and interests of students by applying appropriate learning methods as well as in order to materialize the results of good learning in class VII art music. The two stay two stray method can be used on all subjects and for all ages of learners. Two stay two stray method is a group learning system with the aim that students can work together, responsible, help each other solve problems, and encourage each other to excel. Based on the results of researchers conducted by researchers in two cycles of discussion chapter IV it can be concluded that the two stay two stray method to improve the learning result of art and culture (simple ensemble music) on the students of grade VII.1 SMP Negeri 4 Siak Hulu in the academic year 2016/2017 can improve student learning outcomes. It is known from the number of students who reach KKM menigkatkan on the first cycle of a simple music practice test ensemble that is 19 students, on the second cycle of simple music practice ensemble test that is 28 students complete the KKM, from tests of simple music practice ensemble ensemble, and the amount students who scored the highest score increased on the practice of ensemble music simple cycle II. Keywords: Ensamble Music simple, two stay two stray